Effect of tillage on the incidence and severity of leaf diseases in maize (Zea mays L.) and common bean (Phaseolus vulgaris L.) under different cultivation systems - Mora Eguiguren, L.E. (1978)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 1978